The Ability To Write Scientific Articles among University Students Views from Five Institutions in Indonesia - Hernawan Hernawan; Dadang S. Anshori; Syihabuddin Syihabuddin; Yeti Mulyati (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2023)
The low ability to write scientific articles in students must be addressed immediately. This factor is increasingly prominent when the learning model used is not in accordance with the learning outcomes of the course. This research aims to measure the ability to write scientific articles of university students in Indonesia before and after the application of the Genre-Based Writing Model synthesized with Critical Literacy. A quantitative approach was used in this research with a quasi-experimental research method. The data sources of this research were students from four universities in Indonesia with a total of 144 students. The research data were the students' scientific articles. The data collection technique in this research was the test technique. Based on the results of the research, students' abilities before being treated with the Genre-Based Writing model synthesized with Critical Literacy were in the sufficient category, while after being treated with the model students' abilities were in the excellent category. In other words, there was a significant increase in students' ability to write scientific articles between before and after being treated with the Genre-Based Writing model synthesised with Critical Literacy.